Saksi Kerajaan Allah: Menguak Strategi Misi Nabi Yeremia Dan Relevansinya Bagi Pelayanan Misi Masa Kini - Adilang, Ryanto; Pananggung, Rifke Alfione (Tepian : Jurnal Misiologi dan Komunikasi Kristen, 2024)
This article examines the mission strategy of the Prophet Jeremiah in the context of the significant challenges faced by the nation of Israel. Known as the "witness to the kingdom of God," Jeremiah was called by God to deliver messages that contained both judgment and hope amidst a national crisis. Utilizing the term "strategy," derived from the Greek word "strategos," this article explains how Jeremiah, as a spiritual leader, devised his plan to achieve divine objectives despite facing rejection and threats to his life. Through a qualitative approach, this analysis highlights Jeremiah's courage in taking risks, boldly addressing the moral decay of society, and his resilience in carrying out his mission, even when deemed politically unsuccessful. With extraordinary obedience, Jeremiah demonstrates that while outcomes may not always meet expectations, faith and perseverance in fulfilling God's call hold profound significance. Jeremiah's mission strategy offers valuable lessons about faithfulness and hope for future generations in facing life's challenges.